The Routledge International Handbook of Deindustrialization Studies - Berger, Stefan; Berger, Stefan; Clarke, Jackie; High, Steven; Linkon, Sherry Lee; Strangleman, Tim (London Taylor & Francis Routledge [Imprint], 2025)
The Routledge International Handbook of Deindustrialization Studies is a timely volume that provides an overview of this interdisciplinary field that emerged in response to the widespread decline of manufacturing and heavy industry from the 1980s onward. Edited by prominent figures in the field, the volume brings together many of the leading scholars from a range of countries across the globe to offer a multifaceted overview of deindustrialization and its impact. Deindustrialization has been cited as one of the factors behind the rise of the far right, and to a lesser extent the far left, across Europe, the rise and success of Trumpism in the US, and the Brexit vote as well as the more recent and sudden erosion of UK Labour's 'Red Wall' of the North of England. This collection brings together scholars of deindustrialization around the globe and from a wide variety of academic disciplines including history, sociology, politics, geography, economics, anthropology, literature, arts practice, photography, heritage, and cultural studies. In doing so, the volume explores the roots of deindustrialization across the world, highlights the key themes and issues in the field, illustrates the intersectional and interdisciplinary character of the field, and shows how deindustrialization lies at the heart of many of the key political, cultural, social, and economic issues of our time. Written in a clear and accessible style, the Handbook is a comprehensive interdisciplinary volume for this young but maturing field. The volume is a valuable resource for students, teachers, and researchers interested in industrial decline, closure, and the multifaceted impacts they cause. It speaks to readers across the arts, humanities, and social and political sciences concerned with deindustrialization broadly defined.
eng
Keywords: Business and Management; Economics, Finance, Business and Management; Management and management techniques; Society and Social Sciences; Sociology and anthropology; Sociology; decline of manufacturing; deindustrialization; Gentrification; Industrial culture; industrial decline; jobs; Moral Economy; Queer Study of Deindustrialization; Socialism; unemployment